THE INTERDEPENDENCE BETWEEN HUMAN AND NATURE IN CRAIGHEAD JEAN GEORGE'S MY SIDE OF THE MOUNTAIN - Sugiarto, Tri; Purbani, Widyastuti (Diksi, 2019)
(Title: The Interdependence Between Human and Nature in Craighead Jean George's "My Side of The Mountain"). Centering from the belief that literature is an important media to remind people about the significant role of the environment and to stimulate awareness about its critical condition, this study explores ecological discourse in Jean Craighead George's My Side of the Mountain. It aims to reveal an interdependence between people and nature. Applying qualitative content analysis, this study shows that the interdependence between people and nature is different in degree. People have a strong dependence on nature, whereas nature is an independent entity and scarcely needs people to support their life. Sam in My Side of the Mountain has been nurtured by nature. It provides him food, shelter, and protection from any inconvenient weather. However, Sam is careless and ignorant. He focuses on fulfilling his needs and neglecting his surroundings. In the novel, nature is dominated and positioned as the object to fulfill humans' needs and desires. Keywords: literature, nature, human, interdependence